Water and Wastewater Services in the Danube Region : Hungary Country Note - World Bank (Washington, DC, 2015)
To evaluate and reflect the sustainability of services in the region, an overall sector sustainability assessment was done, taking into account four main dimensions: access to services, quality of services, efficiency of services, and financing of services. Each of these dimensions is measured through three simple and objective indicators. For each indicator, best practice values are established by looking at the best performers in the region, and countries closest to those best performers are deemed to have a more mature sector. A more complete description of the methodology to assess sector sustainability is included in the Annex of the State of the Sector Regional Report from the Danube Water Program. The outcomes of this assessment for Hungary’s water sector are displayed, which also shows average and best practices in the Danube region. The Hungarian sector sustainability score is 74, which is far above the Danube average sustainability of 64, and is among the best practices in the region. The assessment shows that, on average, the country performs well in terms of continuity of access to piped water and flush toilet, collection ratio, nonrevenue water and staffing level. The main deficiencies of Hungary’s water sector identified through the sector sustainability assessment are the operating cost ratio, affordability, and investments. The main sector challenges are: achieving full cost recovery; preventing the degradation of assets in the long term; and preparing for the risks caused by climate change.